Invariância ao contraste no wulst visual da coruja-buraqueira, Athene cunicularia - Claudiana Souza de Amorim (2011)
Selectivity for stimulus orientation is a key emergent property of neurons in the mammalian primary visual cortex (V1). Despite 50 years of considerable research efforts, the mechanisms underlying this property are still a matter of ongoing debates. The fact that orientation-tuning precision is maintained despite wide variations in stimulus contrast, a phenomenon known as contrast invariance, has been considered as an essential piece of experimental evidence to constrain possible models of orientation selectivity. In the present study, we investigate whether contrast invariance is also present in a model system that is evolutionary distant, albeit functionally comparable, from V1, namely the owl visual wulst. A total of 76 cells were isolated in five awake burrowing owls (Athene cunicularia), using standard extracellular recording techniques. Test stimuli were optimal sine-wave gratings varying in both contrast (10%, 30% and 90%) and direction of drift (n=16, 22,5° steps). Orientation/direction tuning was characterized by fitting the sum of two von Mises functions to mean responses using standard iterative least-square methods. We found that average tuning bandwidths slightly, but significantly, increased with contrast. This effect was however not compatible with the iceberg-effect concept (broadening of tuning width due to a membrane potential increase) since no positive correlation between bandwidth and response gains were found. There was no significant shift in preferred orientation and a very modest re-scaling of tuning curves. We also found that directional tuning was not contrast invariant. Cells weakly directional at high contrast significantly increased their response rate for specific direction of movement when stimulated with low-contrast gratings. Altogether, our results indicate that contrast has a small impact on the orientation-tuning precision of wulst neurons. The challenge for future research will be to understand the functional implications of these findings